Operations management - Russell, Roberta S.
Featuring an ideal balance of managerial issues and quantitative techniques, this introduction to operations management keeps pace with current innovations and issues in the field. It presents the concepts clearly and logically, showing readers how OM relates to real business. The new edition also integrates the experiences of a real company throughout each chapter to clearly illustrate the concepts. Readers will find brief discussions on how the company manages areas such as inventory and forecasting to provide a real world perspective